Poverty in India: Misspecified policies and estimates - M. H. Suryanarayana (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Specification counts in the formulation of any economic problem, estimation of its magnitude and its assessment. This is particularly so for problems in the context of economic development. Solutions for poverty alleviation in developing countries like India are often formulated under misspecified premises. This results in wrong choice and design of strategies and policies. Faulty evaluation due to specification errors in estimates of poverty only compounds the error. This paper discusses such an in issue in the context of strategies for and estimates of poverty reduction in the developing countries. The results are general. They are illustrated with reference to India. India has pursued a strategy for growth with redistribution with little appreciation of its limited potential. What have been the consequences? There is a consensus that incidence of poverty with reference to the calorie intake criterion has declined in India from about 55 percent in the mid 1970s to about 25 percent of the population today. The paper lists the implicit assumptions underlying the application of the conventional income/consumption based poverty estimates. It examines how institutional and structural changes during the development process could lead to specification errors in such estimates and hence, faulty evaluation of the consequences. The study concludes that the estimates of poverty with reference to a time-invariant calorie-intake-based norm do not show a real reduction in poverty but only a reduction in overestimation of poverty for the initial years followed by its underestimation for the later years. Even today about 75 percent of the population is calorie deficient. – growth ; redistribution ; poverty ; specification error
Keywords: C1; I32; O0; 330; Armutspolitik; Entwicklungsstrategie; Indien